Enhancing carrot convective drying by combining ethanol and ultrasound as pre-treatments: Effect on product structure, quality, energy consumption, drying and rehydration kinetics - Santos, Karoline Costa (2021)
Ultrasound was combined with ethanol to improve different aspects of carrot convective drying, evaluating both processing and product quality. The ultrasound in water treatment resulted in cellular swelling and small impact on texture. Differently, the ultrasound in ethanol and ethanol treatments modified both carrot microstructure (cell wall modifications of parenchymatic tissue) and macrostructure (shrinkage and resistance to perforation). Pre-treatments with ultrasound in ethanol and ethanol improved the drying kinetics, reducing the processing time (similar to 50%) and the energy consumption (42-62%). These pre-treatments also enhanced rehydration, whose initial rate and water retention were higher than the control. In addition, the carotenoid content was preserved after drying, for all the treatments. Any impact on shrinkage was observed. A mechanistic discussion, based on structural modification (microstructure and macrostructure) and physical properties of water and ethanol, was provided. As conclusion, this work not only described positive aspects of combining the technologies of ultra sound and ethanol as pre-treatments to convective drying, but also proposed mechanisms to explain the phenomena.